A Comparison of Burglary Near Repeat Victimization Between Rural and Urban Areas Using a Target-Based Assessment of Criminal Opportunity - Chainey, Spencer P. (International criminal justice review, 2021)
Numerous studies have shown that near repeat victimization of burglaries can account for a substantial minority of burglaries in urban settings. Using a method based on the distribution of potential targets to determine the size of spatial bandwidths, the presence of burglary near repeats in rural areas was examined and compared to the level of near repeats in urban areas. A significant burglary near repeat pattern was observed in rural areas, but was restricted to the spatial and temporal bands that were closest to and most recently after a previous burglary. The proportion of all burglaries that were near repeats in this nearest spatial and temporal bands was greater than that observed in urban areas. The findings lead to extending how the boost account and offender foraging principles may apply in rural settings, and the identification of crime prevention opportunities that counter near repeats in rural areas.